Does Innovation Encourage Investment in Fixed Capital? - Nickell, S; Nicolitsas, D (Centre for Economic Performance, LSE, 1996)
This paper presents an empirical investigation of the hypothesis that increased R&D; expenditure by companies generates a subsequent increase in fixed capital investment both within the same companies and in the companies which they supply. We use an investment framework which involves modelling explicitly the expected present value returns to a marginal increment in the capital stock. This framework is directly suited to our purpose unlike the more standard Euler equation or Q models common in the literature. Our results indicate that R&D; expenditure does indeed encourage investment in most industries and that there are no posibitive effects in the other direction. We have thus uncovered a part of the investment process but a more complete understanding awaits an improvement in our knowledge of the determinants of R&D;.